2005
DOI: 10.1089/mdr.2005.11.18
|View full text |Cite
|
Sign up to set email alerts
|

Mutation of L4 Ribosomal Protein Conferring Unusual Macrolide Resistance in Two Independent Clinical Isolates ofStaphylococcus aureus

Abstract: The aim of this study was to characterize the resistance mechanisms of two strains of Staphylococcus aureus UCN42 and UCN43 isolated from cystic fibrosis patients that displayed an unusual phenotype of resistance to macrolides. The strains were resistant to erythromycin and the 16-membered macrolide spiramycin but susceptible to clindamycin. None of the strains contained erm or msr(A) genes by PCR. Sequencing of genes encoding ribosomal targets of macrolides revealed mutations in conserved regions of the L4 ri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
19
0
2

Year Published

2006
2006
2016
2016

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 13 publications
0
19
0
2
Order By: Relevance
“…Our isolation of a Lys68Gln mutant is the first report of an L4 mutation in S. aureus associated with resistance through selection with oxazolidinones. Further studies are needed to conclusively link this mutation to the observed increase in LZD resistance; however, a number of other documented L4 mutations involve alterations in amino acids in this region of the protein (18,23,56,76). Mutations in the rplC gene encoding ribosomal protein L3 were found in a large portion of the mutants selected in our spontaneous mutation frequency experiments.…”
Section: ϫ10mentioning
confidence: 93%
“…Our isolation of a Lys68Gln mutant is the first report of an L4 mutation in S. aureus associated with resistance through selection with oxazolidinones. Further studies are needed to conclusively link this mutation to the observed increase in LZD resistance; however, a number of other documented L4 mutations involve alterations in amino acids in this region of the protein (18,23,56,76). Mutations in the rplC gene encoding ribosomal protein L3 were found in a large portion of the mutants selected in our spontaneous mutation frequency experiments.…”
Section: ϫ10mentioning
confidence: 93%
“…In H. influenzae, L4 amino acid variations (insertion 65 GT, K 61 Q, T 64 K, G 65 D; deletion 65 GR, G 53 A; deletion of 66 RA, A 69 S, T 82 I, D 94 E, D 139 G), some outside the loop region, could provide high-level resistance of up to 128 mg/mL for 14-and 15-membered macrolides (Clark et al 2002;Peric et al 2003). S. aureus isolates with L4 amino acid changes R 168 S, G 69 A, and T 70 P have been described in CF patients (Prunier et al 2005). Amino acid variations in L4 from M. genitalium (N 21 K, H 69 R, V 84 G, E 128 G, P 81 S, Y 135 P, N 172 S, N 172 S, A 114 V, A 116 V, A 114 S, R 45 K) were found encoded in DNA from the urine of men with nongonococcal urethritis , and in the chromosomal DNA isolated from a collection of M. genitalium isolates .…”
Section: Ribosomal Protein Mutationsmentioning
confidence: 99%
“…Ribosomal alteration is mediated by a ) and in ribosomal proteins L4 and L22 (encoded by rplD and rplV genes, respectively) have been infrequently described [11][12][13]. Active efflux is mediated by the msr(A) gene that codes for a putative efflux pump and is responsible for the so-called M phenotype characterised by unique resistance to 14-and 15-membered ring macrolides.…”
Section: Introductionmentioning
confidence: 99%